Measures taken by the Soviet government to create the social infrastructure of aviation industry enterprises in the 1950-ies and 1960-ies - V. B. Romanova; N. N. Kabytova (Вестник Самарского университета: История, педагогика, филология)
The article shows the process of infrastructure development of enterprises of the Ministry of Aviation Industry in the 1950-ies and 1960-ies based on documents from federal and regional archives. It was during this period that the social sphere became one of the priorities of the internal policy of Soviet state. An important role was assigned to industrial enterprises, which acted as a guarantor of social benefits determined by decrees, laws, decisions of the government and local authorities. Ministry of Aviation Industry was responsible for creating infrastructure for employees of controlled enterprises. The aviation industry needed qualified and permanent staff. The article analyzes the situation of creating housing and cultural conditions for workers of the plant № 24 named after M.V. Frunze in the post-war years. The process of creating infrastructure can be divided into two periods. At the first stage, in conditions of shortage of construction materials, difficulties with supply and financing, the process was regulated through the publication of administrative documents of the highest authorities, which gave directive instructions. At the second stage, the task of equipping workers required large-scale solutions to create a full-fledged infrastructure based on the application of standard projects and the use of industrial methods, which were carried out in 1950–1960 by the factories of the Ministry. It was possible to quickly establish the process of building social infrastructure. Significant funds were allocated to the Ministry for capital construction.